"Get busy talking or get busy dying". Issue 1 (4th January 2016) - Peake, Greg
Abstract : Purpose: – The purpose of this paper is to high-light the very well-known potential downside of technology found in many sales environments and to provide a fail-safe remedy to telephone Call Reluctance. Design/methodology/approach: – The typical, illogical thinking that underpins the reasons that sales people offer for their Call Reluctance are discussed in detail. A time tested platform built upon sound logic and decades of successful implementation is provided. The approach appeals equally to managers and sales personal because it is simple, doable and highly motivational. Findings: – The results demonstrate the powerful effect that accurate thinking and an easily implemented management approach has for sales organizations and individuals when embracing the unparalleled value of telephone communication. Originality/value: – The work is based upon the authors 40 plus years of applying the thinking and platform presented in the paper. In addition, for the past 15 years, the author has enthusiastically witnessed the incredibly positive impact of his approach to over 400 companies worldwide. He does not claim absolute originality of the content, as like most successful sales people, he is indebted to many, many sales people he has had the pleasure to know and learn from.